Empathizing – systemizing. Simon Baron-Cohen’s theory - IZDEBSKI, PAWEŁ; BĄK, AGNIESZKA; ŻBIKOWSKA, KAROLINA (Studia Psychologica: Theoria et praxis, 2014)
The objective of this article is to present the basic assumptions of the Simon BaronCohen’s Empathizing – Systemizing Theory. This is one of the latest theories describing and explaining sex differences. It is rooted in evolutionary and developmental psychology, and also in psychopathology. The article reviews the most important research supporting the assumptions of the theory.